(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2024)
Erosion problems on slopes are very common because they are structures that are exposed to the elements, therefore, they are constantly affected by natural phenomena such as rain, strong winds and vibrations due to vehicular flow. In this way, it is necessary to implement cover elements on the surface of the slope in order to reduce the risk of failure. Geomats are commonly manufactured from products derived from polymers, these have excellent conditions of resistance and durability but being synthetic materials are highly polluting and are not biodegradable. The purpose of this research article is the review and comparison of different bibliographical citations in which the mechanical characteristics of fique fiber (tensile strength, stiffness, modulus of elasticity, etc.) are evaluated; to determine this way, its behavior and feasibility made its possible use in the future in the manufacture of geo-membranes for the substitution of synthetic materials. In this case, it is possible to identify that the resistance of the fique depends directly on the methodology used for the treatment of the fiber, this is a useful material for the surface protection of slopes since it manages to control erosion problems.